INFLUENCE OF HYDROGEN SATURATION ON CHARACTERISTICS OF ZIRCONIUM - TRUSH, VASYL (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article presents a literature review on the effect of hydrogen saturation on the properties of zirconium alloys. Zirconium alloys are an indispensable structural material for the core of nuclear reactors. During operational loads, the interaction of zirconium materials with interstitial elements (oxygen, nitrogen, hydrogen) necessarily occurs. Zirconium shows the greatest affinity for hydrogen. One of the vulnerable zirconium elements is fuel rod tubes. The safe operation of a nuclear reactor depends on their integrity. In addition, it is fuel tubes that are most exposed to hydrogen. Therefore, the systematization of knowledge about the effect of hydrogen on the properties of zirconium tubes will make it possible to better predict their operational behavior. According to scientific literature data, depending on the volume of absorbed hydrogen, either a solid solution or zirconium hydrides can form. The dependence of the absorbed hydrogen zirconium on the dilution of the hydrogen medium and temperature is shown. The chemical composition of the zirconium alloy also affects the rate and amount of absorbed hydrogen. The effect of hydrogen on the mechanical properties of zirconium alloys is presented. The differences on the fracture surface after tensile tests at room temperature are shown depending on the amount of absorbed hydrogen. Data are presented that indicate that hydrogen atoms are located in octahedral or tetrahedral interstitial voids of a hexagonal close-packed zirconium lattice. It is shown that the thermal solubility of hydrogen in α-zirconium is extremely low, its value is 6 at. % at the eutectoid transformation temperature, and at room temperature the solubility of α-Zr hydrogen does not exceed 1·10-5 wt. %. In high-temperature β-Zr, hydrogen dissolves up to 50 at. %. It has been established that deterioration of the properties of zirconium elements of nuclear reactors during operation due to exposure to hydrogen is likely due to a number of factors: hydrogen embrittlement, the formation of large massive accumulations of hydrides and delayed hydride cracking. It is shown that the direction of arrangement of hydrides depends on the texture of the matrix and on the stresses present in the material that act during the formation of hydrides. It has been established that hydrogen can penetrate into a metal through an oxide film, diffusing, for example, along extended defects such as dislocations and grain boundaries. It is noted that the solubility of hydrogen in zirconium depends on other penetration elements already present in the metal, for example, the solubility of hydrogen in α-zirconium depends on the soluble oxygen in the metal matrix, which is confirmed by the reduced «Zr–O–H» ternary system.